Electron microprobe analysis of polyhalite from the evaporitic Permian Haselgebirge Formation - Christoph Leitner; Franz Neubauer; Johann Genser; Manfred Bernroider (PANGAEA, 2022)
Electron microprobe analyses were conducted at the University of Salzburg, Department of Geography and Geology, in the year 2011. Measurements were performed on a JEOL electron microprobe (JXA-8600), equipped with a wave-length dispersive system. An acceleration voltage of 15 kV and a low sample current of 20 nA were applied to prevent decomposition of polyhalite under the electron beam. Additionally, the spot was defocused to a diameter of 15 μm and after measurement of sulfur, the sample was moved one beam diameter to start measurement of potassium and calcium. Sulfur, potassium and calcium were all measured with the same analyzing crystal. Synthetic and natural mineral standards were used to analyse the emitted wave lengths of the sample and to quantify their amount. Standard ZAF correction calculation revealed the composition in oxide weight percent. The calculation method after Love/Scott1 revealed the formula units of polyhalite (doi:10.1594/PANGAEA.942485).
In: Leitner, C et al. (2022): Electron microprobe analysis and Ar-Ar age dating of polyhalite from the evaporitic Permian Haselgebirge Formation [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.942487